Health education for leprosy: nursing experience - Monteiro, Bruna Rodrigues (2018)
Leprosy is an infectious disease with late diagnosis and evolves into skin lesions reducing thermal, painful and tactile sensitivity in this regard the Ministry of Health, portrays the importance of educational activities in the health sector as a strategic point for your control. It has been as objective report the experience of undergraduate course students and nursing graduate in the development of health education activities about leprosy. Method: A descriptive study of type experience report on health education in leprosy, developed by graduate and undergraduate students in nursing in a scientific event. Data were organized in the following categories: general concept of leprosy and its historical aspect; Signals and symptons; Diagnosis and treatment; Interactive dynamics. It is noticeable interaction of nursing students in the continuing development of health education, combining scientific knowledge with the empirical knowledge, thus contributing to the elimination of leprosy.